(untitled) (Journal of Universal Science Research, 2024)
This article explores the verbalization of gender categories in English, Russian and Uzbek linguistic cultures. The study examines how language is used to convey and construct gender identities in these three diverse linguistic contexts. Through a comparative analysis of linguistic structures, vocabulary and cultural norms surrounding gender, the research aims to uncover similarities and differences in the ways gender is expressed and perceived in each language. By delving into the nuances of gendered language in English, Russian and Uzbek, this study sheds light on the complex interplay between language, culture and gender identity.